Implementation of Basel Accords in India: Enhancing Banking Infrastructure and Technology in India (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The banking industry which was facing turmoil due to spate of bank failures prior to and after independence, with the nationalization of Reserve Bank of India (RBI) on 1-1-1949 got an opportunity to breath in a changed environment. After independence, all changes in the composition of banking system (from single agency to multi-agency system) and matters concerning policies, programs procedures so as to strengthen infrastructure (primary delivery outlets) with a view to cater to the banking needs of common man have been largely mandated by RBI based on specific recommendations of Expert Committee Reports. The Bank advances, deposits and other utility service products are brought onto the integrated technology platform and customers are encouraged to take transactions on alternate channels such as internet, mobile, through ATMs etc.